#TITLE_ALTERNATIVE# - DHARMA BAYUWEGA (NIM : 12208011), WIRA
One of the most difficult drilling areas today is known as "Narrow Drilling Window". Pump Oscillation cycle, utilization of overbalance techique and conventional hydraulic system, which is not steady-state, is not applicable for drilling in this area, which has been proven in many field 9,12,14,35). In 2006, the Managed Pressure Drilling-Continuous Circulation Drilling technique was invented to overcome Narrow Drilling Window area. With this system, static fluid density is allowed to be below formation pressure. In addition, fluid circulation is possible to keep in steady-state and continuous at any time either tripping-mode or drilling-mode in order to maintain constant Equivalent Circulating Density (ECD) by setting the choke position or auxiliary pump rate. The selection of hydraulic operational parameters must be designed to maintain a constant ECD so that the main purpose of MPD technique can be acomplished. Conventional hydraulic system configuration changes due to throttling choke and auxiliary pump system while drilling. To addres this problem, a modification of conventional BHHP, BHI, and JV equation is required. Analytical modifications of the equations with the assumption that is the flow through choke is single phase liquid, incompressible, and steady state. The calculation of the operational parameters to maintain constant ECD during tripping condition is also required so the maximum speed of Pull Out Of The Hole (POOH) could be determined. By using case study of actual data27), it could be obtained that Narrow Drilling Window could be handled by using MPD Continuous Circulation Drilling while the previous conventional techniques had failed. Hydraulics parameters and operating window can be determined so that the operations can be designed as safe as possible. BHHP, BHI, and JV optimization with the choke and the auxiliary pump technique can also be recommended to improve drilling efficiency. Finally, in this study, tripping-mode design to obtain maximum POOH speed can also be determined.